Synthetic Utility of an Isolable Nucleoside Phosphonium Salt - Bae, Suyeal (2008)
[Image: see text] The reaction of O(6)-benzyl-3’,5’-bis-O-(tert-butyldimethylsilyl)-2’-deoxyxanthosine with 1H-benzotriazol-1-yloxytris(dimethylamino)phosphonium hexafluorophosphate (BOP) yielded the nucleoside C-2 tris(dimethylamino)phosphonium hexafluorophosphate salt as a stable, isolable species. This is in contrast to reactions of inosine nucleosides with BOP, where the in situ formed phosphonium salts undergo subsequent reaction to yield O(6)-(benzotriazol-1-yl)inosine derivatives. The phosphonium salt obtained from the 2’-deoxyxanthosine derivative can be effectively used to synthesize N(2)-modified 2’-deoxyguanosine analogues. Using this salt, a new synthesis of an acrolein-2’-deoxyguanosine adduct has also been accomplished.